Reconstruction Of A Village Human Resource Management Model Based On Transformational Leadership And Local Wisdom In Improving Apparatus Performance - Ibrahim Ibrahim; Umar Umar (GENTARA: management and accounting research, 2026)
This study aims to reconstruct a village human resource (HRM) management model based on transformational leadership and local wisdom to improve the performance of village officials. The study used a quantitative approach with an explanatory research design. Data were collected through questionnaires from village officials and analyzed using Structural Equation Modeling (SEM). The results indicate that transformational leadership significantly influences official performance, and local wisdom strengthens this relationship. The reconstruction model emphasizes the integration of trust, transparency, fairness, and local culture into the village HRM management system